2024
DOI: 10.7759/cureus.52198
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative In Vitro Analysis of Antimicrobial Effectiveness and Compressive Resilience in Chirata and Terminalia arjuna Modified Glass Ionomer Cement

Kamala Devi,
Jessy Paulraj,
Rinki S George
et al.

Abstract: Background: Glass ionomer cements are commonly utilized in dental restorations due to their biocompatibility, strong chemical bond with dental tissues, and ability to resist tooth decay. However, their effectiveness can be compromised by the presence of persistent cavity-causing microorganisms. Therefore, it is essential to consider incorporating antibacterial agents into these restorative materials. Swertia chirayita (S. chirayita) and Terminalia arjuna (T. arjuna) are well-known for their rich composition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…According to ISO 9917 (2007), it is imperative to evaluate the compressive strength of dental materials. In the present study, pairwise comparison analysis revealed no significant difference among the gingermodified groups when compared to the control (Group G), aligning with the findings of Devi et al [26], Jaidka et al [27], and Pavithra et al [28]. These investigations suggested that adding antimicrobial agents at certain concentrations did not adversely affect the compressive strength characteristics of GIC.…”
Section: Discussionsupporting
confidence: 91%
“…According to ISO 9917 (2007), it is imperative to evaluate the compressive strength of dental materials. In the present study, pairwise comparison analysis revealed no significant difference among the gingermodified groups when compared to the control (Group G), aligning with the findings of Devi et al [26], Jaidka et al [27], and Pavithra et al [28]. These investigations suggested that adding antimicrobial agents at certain concentrations did not adversely affect the compressive strength characteristics of GIC.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have also highlighted lower color stability in conventional GIC, supporting our present investigation. Ahmed et al indicated that resinmodified GIC shows improved color stability compared to conventional GIC [15,16]. A study done by Bhattacharya and et al concluded that cention performed better color stability when compared to conventional GIC [1].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, secondary caries may form because cariogenic bacteria can survive beneath the GIC restoration and remain viable for up to two years [5]. Existing research suggests that the fluoride generated by GIC lacks the potency to inhibit bacterial decay effectively over an extended duration [6]. This inadequacy led to the incorporation of antimicrobial agents into GIC.…”
Section: Introductionmentioning
confidence: 99%